How Bad is Good Enough? Exploring Mobile Video Quality Trade-offs for Bandwidth-Constrained Consumers - Donner, Jonathan; Cutrell, Ed; Oeldorf-Hirsch, Anne (Proc NordiCHI 2012, 2012)
In developing countries, many would-be mobile internet users perceive downloadable video content as too expensive. Aggressively degrading this video could reduce its file size and therefore its cost. The studies presented here explore extreme cases of this quality/cost trade-off for mobile phone users in urban India. A series of online studies tested the effects of manipulating a video’s content, bit rate, frame rate, and audio quality on quality ratings and enjoyment. Results show that video quality and thus file size can be greatly reduced with relatively little decrease in these outcomes. A field experiment with low-income users in urban India explored consumers’ choices when presented with a trade-off between video quantity and quality and found that nearly one-third selected a lower quality video for the benefit of more video content. Results suggest that offering lower-quality videos to bandwidth-constrained users could provide monetary savings with only minimal reduction in consumer satisfaction.